New evidence for coiling direction of benthic foraminifera as a temperature proxy - Dong, Shuaishuai; Lei, Yanli; Wu, Tianzhen; Li, Meng (Frontiers in Marine Science, 2023)
Foraminifera are sensitive to climate change and their species composition, shell chemical element composition and morphological characteristics are useful paleoenvironmental proxies. Coiling direction is a distinctive and easily identifiable morphological feature in trochospiral foraminifera and has been used for paleoceanographic reconstruction. Here, we conducted a field survey in a low intertidal zone in Yellow Sea for 13 months and performed a culture experiment under three temperatures and four salinities for the benthic foraminifera to seek the relationship between coiling direction and environmental factors. Our results showed that the dominant benthic foraminifera Ammonia aomoriensis (Asano, 1951) preferred sinistral direction under high temperature and had no preference with salinity. Statistical analysis showed that the ratio of sinistral/dextral in A. aomoriensis was significantly positively correlated with temperature (r = 0.5017, p = 0.0011 for field survey and r = 0.5117, p = 0.0014 for culture experiment), but had no evident relationship with salinity (p > 0.05). The ratio of sinistral/dextral was significantly negatively related with the abundance of A. aomoriensis (p < 0.05) and the ratio of sinistral/dextral was significantly positively related with the size (p < 0.05). This was the first study on the coiling direction of benthic foraminifera combining the field survey and culture experiment. Our findings suggested that the ratio of sinistral/dextral in A. aomoriensis could be used to indicate the change of temperature. This study offered new evidence for the reliability of the coiling direction as a temperature proxy and made us rethink the significance of the morphological change in biological adaptation and evolution.